INTERAKSI MASYARAKAT DENGAN TAMAN NASIONAL GUNUNG HALIMUN-SALAK (Studi Kasus di Desa Gunung Bunder II, Kecamatan Pamijahan, Kabupaten Bogor, Provinsi Jawa Barat) - , IBNU OKTAFIYANTO; , Dr. Ir. Lies Rahayu WF., MP ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Community in the village Gunung BunderII has interacted with forest area in The Gunung Halimun-Salak National Park (GNHSNP) since before the area estabilished as a national park. The interactions made by the forest communities to the GNHSNP which can be either positive or negative. This research aims to determine the interactions that occur between community around the park with the park. This research carried out by the case study, means looking at forms and pattern of communities interaction with the forest intensiety and deep. The unit examined in this study was the groups of community who directly interacting and depending their life from TNGHS area. This research obtained the five forms of interactions, there are between GHSNP with volunteer group, GHSNP with tappers group, GHSNP with merchant groups, GHSNP with perencek group (people who search branch and grass), and the managers of GHSNP with community surrounding. One of five these interactions, the Mount Halimun-Salak National Park areaâs interaction with the perencek groupis negative and only advantagethe perencek groups. Whereas, four other interactions, interaction with volunteer group, tappers group, merchant group, and managers are positive and benefical interactions.